2014
DOI: 10.1177/156482651403500308
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Nutrient Intake and Acceptability of Nutritionally Balanced School Meals in Filipino Students

Abstract: Nutritionally balanced nutri-meals may be a healthier and acceptable alternative to regular Filipino school meals. Further optimization of nutri-meals is required to meet the nutritional needs of adolescents and reduce sodium content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This is consistent with previous findings that national food programs, including the PNAE, tend to prioritize the provision of a healthy diet, defined as a greater quantity of fresh or minimally processed foods such as fruits, vegetables, and milk, and reduced levels of sodium and simple sugars 1719,32–34 . In the Philippines, a school meal program developed nutritious meals for adolescents to ensure higher intakes of micronutrients ( p < 0.001), fiber ( p < 0.001), and the intake of higher-quality fats ( p < 0.001) as compared with basal meals 35 . In France, school meals were associated with the consumption of fresh vegetables and fruits ( p < 0.001) and family income ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous findings that national food programs, including the PNAE, tend to prioritize the provision of a healthy diet, defined as a greater quantity of fresh or minimally processed foods such as fruits, vegetables, and milk, and reduced levels of sodium and simple sugars 1719,32–34 . In the Philippines, a school meal program developed nutritious meals for adolescents to ensure higher intakes of micronutrients ( p < 0.001), fiber ( p < 0.001), and the intake of higher-quality fats ( p < 0.001) as compared with basal meals 35 . In France, school meals were associated with the consumption of fresh vegetables and fruits ( p < 0.001) and family income ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Interventional studies aiming to change the profile of available foods in school cafeterias by reducing the availability of ultra-processed and processed foods and increasing that of fresh or minimally processed foods and/or meals have yielded positive results concerning improved nutritional profiles and adherence to a healthy diet among adolescents 23,35,41,43,44 . These changes in available foods yielded net reductions in the caloric, sugar, and sodium contents of the offered meals 41 .…”
Section: Discussionmentioning
confidence: 99%
“…With the transition from secondary school to college or university, as independency increases, students are constantly challenged to make healthy food selections (1) . Such transition into young adulthood is frequently a period of unhealthy lifestyle where young people could assume long-lasting health behavior habits.…”
Section: Introductionmentioning
confidence: 99%
“…Given that one of the main goals of colleges and universities is to broaden the knowledge of the society, the enhancement of the nutrition attitudes, knowledge and practices of the students is of high importance, as this will subsequently lead to a more food-conscious society and healthier people. Some studies have shown that most students are not familiar with the healthy foods needed for their body in different conditions (1,4) . Research showed that the majority of students (83.6%) eat three meals during the day regularly and no difference was found between men and women (6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation